Allies and adversaries : the Joint Chiefs of Staff, the Grand Alliance, and US strategy in World War II - Stoler, Mark A. (Chapel Hill, N.C. ; London : University of North Carolina Press, 2003)
"Drawing on sources that include the unpublished records of the Joint Chiefs as well as the War, Navy, and State Departments, Mark Stoler analyzes the wartime rise of military influence in U.S. foreign policy. He focuses on the evolution of and debates over U.S. and Allied global strategy. In the process, he examines military fears regarding America's major allies - Great Britain and the Soviet Union - and how those fears affected President Franklin D.
Roosevelt's policies, interservice and civil-military relations, military-academic relations, and postwar national security policy as well as wartime strategy."--BOOK JACKET.
Originally published: 2000.
Includes bibliographical references and index.
Keywords: Roosevelt, Franklin D; United States. -- Joint Chiefs of Staff -- History -- 20th century; USA -- Joint Chiefs of Staff; 1900-1999; World War, 1939-1945 -- United States; Strategy -- History -- 20th century; Civil-military relations -- United States; Military relations; United States -- Military relations -- Foreign countries; United States -- Foreign relations -- 1933-1945.; History